Google+ vs Facebook: The Comparison - Kevin Curran; Scott Morrison; Stephen Mc Cauley (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2012)
Social networks are a varyingly popular tool used to connect with friends, colleagues and/or family. Recently, Facebook has been at the top of the social network food chain, with Bebo and MySpace decreasing in users and the huge increase of users joining Facebook in such a short time. Google have just recently launched Google+, a social networking site. This is not the first time that Google have attempted to break into the social networking scene but it is possible that these failed attempts may have taught them something. As Facebook’s user base is extremely diverse, spreading across different countries, races, ages, professions, and interests, to name a few, this network is a good model to compare new rival Google+ to. Google+ has set out to do the same things as Facebook but better to try and steal away some of that high power and necessity that Facebook has gained. Facebook has News feed, Google has Stream. Facebook has Lists, Google has circles. Facebook has like’s, Google has +1. Facebook accounts for 10% of overall internet usage. This paper will look at various comparables between the two social networks and analyse the better functionality, design and ease of use. It will then conclude a verdict on which is the better social network to use overall.